Elderly Alcoholism : Intervention Strategies. - Beechem, Michael (Charles C Thomas Publisher, LTD, 2002)
This text is the first of its kind to substantively integrate alcoholism, aging, and grief theories into an easy-to-understand format for interdisciplinary undergraduate and graduate students in the behavioral and physical sciences. Written to prepare students in working with an elderly clientele, the reader is provided with elder-specific practice methodology derived from experiential and theoretical content. Chapters 1 through 4 alert the readers to the nature of elderly alcoholism and accompanying aging theories. Chapter 5 underscores the challenges faced by professionals in identifying eld.
Keywords: Older people -- Alcohol use.; Alcoholism -- Treatment.; Older people.; Alcoholism -- therapy; Substance-Related Disorders; Aged; Personnes âgées -- Consommation d'alcool.; Alcoolisme -- Traitement.; Toxicomanie.; Personnes âgées.; elderly.; SELF-HELP -- Substance Abuse & Addictions -- Alcoholism.; Older people; Alcoholism -- Treatment; Older people -- Alcohol use